2013
DOI: 10.1159/000353211
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Composition in Patients with Chronic Obstructive Pulmonary Disease: Do They Influence Patient-Related Outcomes?

Abstract: Aims: The follow-up of the ECLIPSE study, a prospective longitudinal study to identify and define parameters that predict disease progression over 3 years in chronic obstructive pulmonary disease (COPD), allows the examination of the effect of body composition changes on COPD-related outcomes. Methods: Body composition and health status were established in 2,115 COPD patients, 327 smoking and 239 nonsmoking controls at baseline and 3 years, while mortality was recorded in year 2 and 3 in the COPD patients. Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 31 publications
7
50
2
2
Order By: Relevance
“…In the majority of previous studies, dyspnea scores were found to be higher in obese subjects compared to normal-weight subjects (7,8). However, there are studies demonstrating no difference between obese and normal-weight patients in terms of dyspnea (21).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the majority of previous studies, dyspnea scores were found to be higher in obese subjects compared to normal-weight subjects (7,8). However, there are studies demonstrating no difference between obese and normal-weight patients in terms of dyspnea (21).…”
Section: Discussionmentioning
confidence: 94%
“…However, obesity might also increase the numbers of obstructed peripheral airways (6). It was determined that dyspnea perception is enhanced, health status is impaired, and quality of life (QOL) is reduced in obese COPD patients compared to non-obese COPD patients (7,8). It has been shown that pulmonary rehabilitation (PR) reduces dyspnea, enhances exercise performance, improves QOL, and decreases psychological symptoms in COPD patients (9).…”
mentioning
confidence: 99%
“…We began by examining the association of pectoralis muscle area and measures of fat-free mass at baseline in a subset of 73 subjects enrolled in the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE) Study (10). Bioelectrical impedance analysis (BIA) was performed on each subject, using the Bodystat 1500 (Bodystat Ltd, Isle of Man, UK), and the resistance was used to calculate fat-free mass (14) as previously described (15). The goal of this analysis was to establish the correlation between fat-free mass and pectoralis muscle area; therefore we investigated only that subset of the total ECLIPSE population that had pectoralis muscle area, bioimpedance, and CT measures at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of fat-free mass by BIA is an indirect method of body composition and is not recommended in the clinical setting (30). However, body composition as assessed by BIA has been related to COPD-related traits and outcomes, including mortality, indicating that the method has use in the research setting (15,18,27,30).…”
Section: Original Researchmentioning
confidence: 99%
“…Spirometry was performed after inhalation of 4 puffs of albuterol 29 ; lung volumes by body plethysmography and diffusing capacity by single breath carbon monoxide uptake (DLCO) (Vmax 229 and Autobox 6200; SensorMedics; Yorba Linda, California) were performed according to American Thoracic Society (ATS)/ European Respiratory Society (ERS) standards.…”
Section: Assessmentsmentioning
confidence: 99%